New Ideas for Quantifying the Gushing Potential of Malt - Christian, Manuel; Ilberg, Vladimír; Titze, Jean; Parlar, Harun; Jacob, Fritz (BrewingScience, 2009)
In this work it was first shown how to quantify the gushing potential of malt with a modification of a common gushing test. Today there exist two acknowledged gushing tests for the brewing industry (Modified Carlsberg Test and Weihenstephaner Test). Both analytical methods use the overfoaming amount of a test-specific produced carbonated wort to determine the gushing potential of malt. Unfortunately the overfoaming amount can vary statistically in a way that this parameter can "only" be used for qualitative information if the malt has a potential for gushing or not and if one malt has a higher or lower gushing potential than another one; but a precise quantitative comparison for example between two malts which both have a gushing potential is difficult. This was the focus of this investigation. With two gushing-positive samples (malt A and B) it could be shown that with an increase of the concentration of malt solutes a certain point is reached where gushing appears the first time determined by the overfoaming amount applied the Modified Carlsberg Test. For malt A a frequently higher gushing potential (f ≥?5) than for malt B was identified. These results were verified by determining the amount of a gushing suppressing hop product that led gushing to zero by having a constant concentration of malt solutes. The results demonstrated enhanced gushing analyses to quantify the gushing potential reproducibly, not by the overfoaming amount but by the "zero point" where gushing begins (concentration of malt solutes) or is neutralized (amount of hop product). The introduced methods enable the chance for the first time to quantify the gushing potential of malt more precisely